SIMULATION TRAINING AT THE STAGE OF FORMATION AND IMPROVEMENT OF INDIVIDUAL PROFESSIONAL SKILLS IN STUDENTS OF MEDICAL UNIVERSITIES - Кочерга, З. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article presents the main principles and tasks on which the training of medical specialists is based. It discusses the importance of practical and technical skills, communication, and the ability to work in a team and use simulation as a method for acquiring practical skills. Basic clinical and theoretical training of medical professionals includes such non-technical skills as communication, clinical thinking and planning. In order to learn and improve technical / psychomotor skills and communication skills, constant practice and simulation is required, which allows us to prove the technique of performing these techniques to automatism. The growing demands for risk reduction for a patient associated with a traditional mentor for the development of clinical and technical skills are increasing as a public requirement for increasing the objectivity and transparency of competence. The structure and methodology of simulation training in medicine determine the necessary professionalization of the training of doctors. Targeted simulations in the aspect of professional training of health workers are a necessary basis for basic medical education, taking into account the needs of health care.